The Effect of Counseling with Video Media On Diarrhea Prevention Knowledge: Pre-Experimental Study of the Desa Kresek, Kabupaten Tangerang - Putri, Shavira Wadya; Ernawati, Kholis; Atmalia, Khafifah Puja; Karidza, Bilqish; Ahmad, Lulu Nuraviah; Triangga, Riyan; Febylia, Nanda (Majalah Sainstekes, 2023)
Introduction: Low knowledge of diarrhea prevention is why diarrhea rates are still high in Indonesia. There have been many ways to increase public knowledge related to diarrhea prevention, one of which is by conducting counseling using video media. This study aimed to determine the effect of video media counseling on knowledge of diarrhea prevention: a pre-experimental study in the community of Kresek Village, Tangerang Regency. Methods: Thei  researchi  designi  wasi  pre-experimenti  onei  groupi  pre-test-post-test.i  Thei  populationi  wasi  thei  community in Kampung Nambo, Kresek District, Tangerang Regency, Banten Province. The study was conducted in January 2023. Criteria for respondents over 13 years of age. The study sample amounted to 40 people taken by consecutive sampling, which was taken for seven days. The intervention was conducted with education using video media titled "Let's Prevent Diarrhea" (Copyright No EC00202310110). The collected datai  werei  analyzedi  usingi  thei  T-testi  withi  thei  helpi  ofi  SPSSi  versioni  26.0.i  toi  determinei  thei  effecti  ofi  counselingi  withi  videos on increasing respondents' knowledge. Results: The results showed ani  increasei  ini  thei  numberi  ofi  correcti  answersi  toi  questionnaire questions after providing educational videos. Before education with video, the number of respondents with good knowledge was only two people (5%). After counseling, it increased to 37 people (92.7%). The Wilcoxon test results showed that the p-value was 0.000. Conclusion: There is an effect of counseling with video media on increasing respondents' knowledge.